(untitled) (Revista da Faculdade de Odontologia - UPF, 2024)
Aim: This study evaluated the irrigation penetration during root canal instrumentation and the clinical step in which the irrigation solution can be detected in the apical region. Materials and Methods: Twenty necrotic molars were divided according to the irrigation protocol, saline solution with manual active pressure, and 2.5% sodium hypochlorite with dripping delivery. Solution penetration assessment used a radiopaque component added to each irrigant solely before a periapical radiograph. Instrumentation sequence was: #10, and #15 K-files (step 1), cervical flaring using WaveOne Small (step 2), WaveOne Small at working length (step 3), Hero-642 #35/.02 (step 4), and Hero-642 #40/.02 (step 5). The step each contrasted-irrigant reached the 2-mm-apical region was registered. Shapiro-Wilk and Fisher’s exact tests were used for comparisons. Results: In step 3, both contrasted-irrigants started to be detected in the apical region, and after step 5, contrasted-irrigants penetrated in 100% of the cases, without significant difference. Conclusion: Considering distal molar roots, the apical enlargement up to an instrument #40.02 favors the irrigation to reach the 2-mm apical region.